2007
DOI: 10.1161/01.res.0000261350.61711.9e
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role for gp130 in Neointima Formation Following Arterial Injury

Abstract: Abstract-Interleukin (IL)-6 induced vascular smooth muscle cell (VSMC) motility in a dose-dependent manner. In addition, IL-6 stimulated tyrosine phosphorylation of gp130, resulting in the recruitment and activation of STAT-3. IL-6 -induced VSMC motility was found to be dependent on activation of gp130/STAT-3 signaling. IL-6 also induced cyclin D1 expression in a time-and gp130/STAT-3-dependent manner in VSMCs. Suppression of cyclin D1 levels via the use of its small interfering RNA molecules inhibited IL-6 -i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 43 publications
0
47
0
1
Order By: Relevance
“…44,45 In addition, we recently reported that cyclin D1 mediates SMC migration induced by interleukin-6 and balloon injury. 46 These findings suggest that cyclin D1, in addition to its role in cell-cycle regulation, is involved in the modulation of cell motility. Although cyclin D1 seems to be one of the molecules required for cell-cycle progression, and possibly cell migration, other molecules whose actions are required for cell proliferation and migration may also be targets of STAT-5B in VSMCs.…”
Section: Figurementioning
confidence: 95%
“…44,45 In addition, we recently reported that cyclin D1 mediates SMC migration induced by interleukin-6 and balloon injury. 46 These findings suggest that cyclin D1, in addition to its role in cell-cycle regulation, is involved in the modulation of cell motility. Although cyclin D1 seems to be one of the molecules required for cell-cycle progression, and possibly cell migration, other molecules whose actions are required for cell proliferation and migration may also be targets of STAT-5B in VSMCs.…”
Section: Figurementioning
confidence: 95%
“…BI was performed essentially as described previously (28). Briefly, rats weighing 250 -300 g were anesthetized by injecting (intraperitoneally) ketamine (60 mg/kg) and xylazine (5 mg/kg).…”
Section: Transient Transfections and Luciferasementioning
confidence: 99%
“…Delivery of Adenoviruses into Injured Arteries-After balloon injury, solutions of 100 l of Ad-GFP (10 10 plaque-forming units/ml), Ad-VIVIT (10 10 plaque-forming units/ml), or Adcyclin D1 (10 10 plaque-forming units/ml) were infused into the ligated segment of the common carotid artery for 30 min as described previously (28).…”
Section: Transient Transfections and Luciferasementioning
confidence: 99%
“…Cultures were maintained at 37 °C in a humidified 95% air and 5% CO 2 atmosphere. The experiments were performed by using subcultured vascular smooth muscle cells between 5 and 9 passages by following a previously published paper [23]. The rationale for using subcultured smooth muscle cells isolated from rat aorta is based on the evidence that there are extensive phenotypic similarities among subcultured aortic smooth muscle cells and the cells in neointima.…”
Section: Cell Culturementioning
confidence: 99%
“…Inhibition of excessive IL-6 signaling by blocking the gp130/JAK/STAT pathway has become a promising intervention to reduce inflammation. A recent study reported that vascular injury increased STAT 3 phosphorylation and that blockade of gp130/STAT 3 signaling decreased balloon injury-induced STAT 3 phosphorylation, reduced smooth muscle cell migration from media to intima, and attenuated neointima formation [23], suggesting that IL-6 plays a pivotal role in vascular injury-induced neointima formation by activating gp130/STAT 3 pathway. PTP1B is a non-receptor protein tyrosine phosphatase that serves as a negative regulator in several signal transduction pathways.…”
mentioning
confidence: 99%